1993
DOI: 10.1063/1.354080
|View full text |Cite
|
Sign up to set email alerts
|

Energy levels and upconversion fluorescence in trivalent thulium-doped yttrium scandium aluminum garnet

Abstract: Absorption spectra of Tm3+ ions in yttrium scandium aluminum garnet are reported between 1.9 and 0.25 μm at 4 K. Laser-excited fluorescence was observed at 4 K from Tm3+(4f12) multiplet manifolds 1D2, 1G4, 3F2, and 3H4 to the ground-state manifold 3H6. Emission from 1D2 and 1G4 also includes transitions to Stark levels in manifolds 3F4 and 3H5. Upconversion excited fluorescence was observed between 1D2 and 3F4 at 10 K. Analysis of the fluorescence emission confirms assignments given to individual Stark levels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

1994
1994
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 10 publications
0
16
0
Order By: Relevance
“…The 3 F 4 → 3 H 6 transition near 1.9 m has applications in medicine and remote sensing [6]. The up-conversion process belonging to the 1 D 2 → 3 F 4 transition in Tm 3+ ions was observed in [7]. The 3 H 6 → 3 H 4 transition at about 800 nm is suitable for commercial laser diode GaAlAs pumping [8].…”
Section: Introductionmentioning
confidence: 95%
“…The 3 F 4 → 3 H 6 transition near 1.9 m has applications in medicine and remote sensing [6]. The up-conversion process belonging to the 1 D 2 → 3 F 4 transition in Tm 3+ ions was observed in [7]. The 3 H 6 → 3 H 4 transition at about 800 nm is suitable for commercial laser diode GaAlAs pumping [8].…”
Section: Introductionmentioning
confidence: 95%
“…It has been confirmed that the Sc 3+ doping would broaden the bandwidths of the absorption and emission spectra of the active ions (Yb 3+ , Nd 3+ ), which is favorable for the generation of the ultrafast pulse laser in the mode‐locking laser regime . In particular, it is believed that the larger radius of the Sc 3+ compared with Al 3+ may increase the distance between lattice sites, which decreases the Tm‐Tm interaction in highly doped Tm:YSAG single crystals . The Tm:YSAG ceramics are potential mid‐infrared laser materials, and some researches on the Tm:YSAG single crystals or ceramics have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Morrison et al investigated the energy levels and branching ratios of Tm 3+ in the YSAG hosts in 1991 . Gruber et al grown the 2 at.% Tm:YSAG single crystal by the Czochralski method and discussed the spectroscopic properties in 1993 . Ferrier et al studied in detail the effects of scandium doping on the inhomogeneous and homogeneous linewidth broadening, Zeeman levels life time in Tm:YSAG ceramics and single crystal in 2018 .…”
Section: Introductionmentioning
confidence: 99%
“…This ion enables obtaining the laser generation in the 2 m spectral region at the 3 F 4 -3 H 6 transition, while the 3 H 6 -3 H 4 transition at ∼800 nm can be used for semiconductor lasers pumping with the subsequent generation in the eyesafe spectral region around 1.5 m. The same transition is currently under study for the creation of optical quantum memory since it allows writing and read-out with the use of semiconductor lasers, in contrast to extensively studied praseodymium ions. Higher-lying levels of thulium ion can be populated under infrared pumping via upconversion processes, leading to the upconversion luminescence [1]. Addition of ytterbium ions into the crystal enhances the upconversion luminescence and enables laser generation in crystals co-doped by thulium and ytterbium (see, e.g.…”
Section: Introductionmentioning
confidence: 99%